2023
DOI: 10.1002/mma.9301
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Fourier decomposition‐type sparse representations versus the Karhunen–Loève expansion for decomposing stochastic processes

Abstract: The present study devotes to introducing and analyzing the use of the adaptive Fourier decomposition (AFD)‐type methods in the area of stochastic processes and random fields. We involve two types of algorithms, namely, stochastic AFD (SAFD) and stochastic pre‐orthogonal AFD (SPOAFD), for, respectively, the Hardy space format and non‐Hardy space ones, as may be regarded. We provide both their theoretical results and practical algorithms and compare them with the well adopted and, in fact, dominating Karhunen–Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
(144 reference statements)
0
1
0
Order By: Relevance
“…Our findings indicated that the AFD variant algorithm proposed by Qian et al does not fully correspond with the specific COVID-19 data from London ( 14 17 ). By reconfiguring components of the AFD, new combinations were developed ( Figure 3B –3C), which surpassed the efficacy of the basic AFD model by Qian et al ( Figure 3A ) ( 11 12 , 18 20 ).…”
Section: Discussionmentioning
confidence: 97%
“…Our findings indicated that the AFD variant algorithm proposed by Qian et al does not fully correspond with the specific COVID-19 data from London ( 14 17 ). By reconfiguring components of the AFD, new combinations were developed ( Figure 3B –3C), which surpassed the efficacy of the basic AFD model by Qian et al ( Figure 3A ) ( 11 12 , 18 20 ).…”
Section: Discussionmentioning
confidence: 97%